The Asia Pacific Consensus Statement on Laparoscopic Liver Resection for Hepatocellular Carcinoma: A Report from the 7th Asia-Pacific Primary Liver Cancer Expert Meeting Held in Hong Kong - Cheung, Tan To; Han, Ho-Seong; She, Wong Hoi; Chen, Kuo-Hsin; Chow, Pierce K.H.; Yoong, Boon Koon; Lee, Kit Fai; Kubo, Shoji; Tang, Chung Ngai; Wakabayashi, Go (Karger Publishers, 2017)
Background: Laparoscopic liver resection has been gaining momentum, and it has become an accepted practice after the two international consensus conferences where experts worked up guidelines to standardize this approach and improve its safety. However, most laparoscopic hepatectomies were performed in patients with liver metastases. The concurrent presence of liver cirrhosis with hepatocellular carcinoma (HCC) poses a great challenge to clinicians trying to establish a routine use of laparoscopic liver resection for HCC. Summary: The first Asia Pacific consensus meeting on laparoscopic liver resection for HCC was held in July 2016 in Hong Kong. A group of expert liver surgeons with experience in both open and laparoscopic hepatectomy for HCC convened to formulate recommendations on the role and perspective of laparoscopic liver resection for primary liver cancer. The recommendations consolidate the most recent evidence pertaining to laparoscopic hepatectomy together with the latest thinking of practicing clinicians involved in laparoscopic hepatectomy, and give detailed guidance on how to deploy the treatment effectively for patients in need. Key Message: The panel of experts gathered evidence and produced recommendations providing guidance on the safe practice of laparoscopic hepatectomy for patients with HCC and cirrhosis. The inherent advantage of the laparoscopic approach may result in less blood loss if the procedure is performed in experienced centers. The laparoscopic approach to minor hepatectomy, particularly left lateral sectionectomy, is a preferred practice for HCC at experienced centers. Laparoscopic major liver resection for HCC remains a technically challenging operation, and it should be carried out in centers of excellence. There is emerging evidence that laparoscopic liver resection produces a better oncological outcome for HCC when compared with radiofrequency ablation, particularly when the lesions are peripherally located. Augmented features in laparoscopic liver resection, including indocyanine green fluorescence, 3D laparoscopy, and robot, will become important tools of surgical treatment in the near future. A combination of all of these features will enhance the experience of the surgeons, which may translate into better surgical outcomes. This is the first consensus workforce on laparoscopic liver resection for HCC, which is a unique condition that occurs in the Asia Pacific region.